Multilateralising Regionalism on Government Procurement - Ueno, Asako (OECD Trade Policy Papers, 2013)
The potential multilateralisation of government procurement commitments in regional trade agreements (RTAs) presents many issues and challenges. To what extent do RTAs go beyond the 2012 revised Agreement on Government Procurement (GPA), and how do they differ among trading partners? This report surveys 47 RTAs in force with government procurement provisions where an OECD member is a party. Coverage commitments (entity coverage, thresholds, and goods and services coverage commitments) and procurement provisions including transparency mechanisms of government procurement in the OECD member RTAs are analysed in detail. In general, non-GPA parties have achieved the general GPA level of market access commitments in their RTAs. In particular, RTA services coverage commitments involving non-GPA parties are more extensive than those of GPA parties. RTA market access commitments signed by the same party are fairly homogeneous while some heterogeneity is observed possibly due in large part to reciprocity (e.g. the sub-central government entity coverage and the level of thresholds). With regard to procurement provisions including transparency measures, most RTAs broadly track those of the GPA, and recent RTAs incorporate new elements introduced in the revised GPA as well. If RTAs are to be seen as the "testing ground" for further multilateral liberalisation, it is concluded that there is a large potential for further expanding the government procurement market. Having observed that the potential costs would seem to be relatively limited at least for the non-GPA parties reviewed in this study, it may well be that this means there is more scope for considering accession to the GPA.